Przybliżone Określanie Odkształceń Płyt i Powłok Plastycznych W Oparciu O Niestowarzyszone Prawo Płynięcia - J.A. König (Engineering Transactions)
The common method of solving various problems of plane stress in the theory of plasticity is stated and justified in a general manner. This method consists in replacing an arc of the Huber- Mises ellipse with a straight line segment, the accurate expression being preserved, however, for the plastic potential. The advantage of such solution which deviats but very slightly from the accurate ones has already been confirmed in various works (cf. [2, 3, 16]). The solutions obtained by the present author in certain cases of load acting on a circular plate and a cylindrical shell show also good accuracy. On the basis of these statements the problem of a cylindrical vessel clamped at the bottom and loaded by the pressure of a liquid is solved in the present paper.